Vitamin K and bone metabolism: the myth and the truth. Issue 3 (3rd May 2016) - Cosso, Roberta; Falchetti, Alberto
ABSTRACT: Several natural/syntheticproducts, containing different metabolites of vitamin K, are freely available and their use is suggested for non-specific 'bone health'. It is therefore necessary and useful to address this specific aspect of their use, describing the state of the art in basic, translational, and clinical studies, reported in the literature. In fact, we do not have any certainty about a real effectiveness of vitamin K in preventing fragility fractures. To date, published clinical trials have been conducted on different ethnicities, with different dietary habits, different supplementations and doses of vitamin K, and with different fracture risk factors. This review aims to provide basic cultural tools to improve the knowledge of readers concerning the use of vitamin K for bone health, helping them to develop an independent critical spirit.